Efforts to fill the information gap - Ingo v. Jacobi (Intereconomics, 1971)
Businessmen all over Europe as well as in North America and in other countries have to be Increasingly concerned with international taxation. Therefore the International Bureau of Fiscal Documentation is gaining In importance.
Keywords: 330; International taxation